MENDAPAT PEMBELAJARAN BERBASIS MASALAH DENGAN SISWA YANG MENDAPAT PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DITINJAU DARI GAYA BELAJAR SISWA SMP NEGERI SE-KOTA METRO, LAMPUNG TAHUN PELAJARAN 2014/2015 - Pratama, Yulian Surya; Budiyono, Budiyono; Slamet, Isnandar (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The purpose of this research was to know the effect of the learning models on the problem solving ability and mathematics communication ability viewed from the learning style. The learning models compared were Problem Based Learning, Think Pair Share learning and Classical. The type of this study was a quasi-experimental study with a 3 x 3 factorial design. The study population was all grade VIII students of Junior High School in Metro city. Sample was collected by stratified cluster random sampling and consisted of 245 students which where divided into three groups,Â 83 students in Experimental Group 1, 81 students in Experimental Group 2, and 81 students in Control Group . The instruments of the research include problem solving ability test, mathematics communication ability test and learning style test. The technique of analyzing data used the two-way multivariate analysis of variance with unbalanced cell. The results of this research could be concluded as follows. (1) Problem Based Learning and Think Pair Share have better problem solving and mathematics communication ability aspects than the Classical learning, Besides that, Think Pair Share and Classical LearningÂ have the same problem solving and mathematics communication ability; (2) The students who have visual learning style have better problem solving and mathematics communication ability than students who have kinesthetic learning style. In addition, students with auditory learning style have the same problem solving and mathematics communication ability as kinesthetic learning style (3) In each of the learning style, the learning model of Problem Based Learning give a better problem solving and mathematics communication ability than the Classical model, and the cooperative learning model of Think Pair Share and Classical Learning give the same problem solving and mathematics communication ability; (4) In each learning model, the students with visual and auditory learning style have better problem solving and mathematics communication ability than students who have kinesthetic learning style, and the students with visual and auditory learning style have the same problem solving and mathematics communication ability.Keywords: Problem Based Learning, Think Pair Share, Learning Style, Problem Solving Ability, Mathematics Communication Ability.